The comparative role of friction in local out-of-plane mechanisms of masonry buildings. Pushover analysis and experimental investigation. (1st November 2016) - Casapulla, C.; Argiento, L.U.
Highlights: Frictional resistances in out-of-plane failure modes of masonry walls are evaluated. The stabilizing role of friction is highlighted in comparison with other systems of strength. Pushover curves are defined according to the displacement-based approach. Experimental results confirm the stabilizing contribution of friction to static multiplier. Abstract: In masonry buildings without a box-type behaviour and subjected to seismic loadings, in-plane and out-of-plane failure mechanisms can take place where frictional resistances might play a predominant role. In this paper a detailed limit analysis of a simple out-of-plane failure mechanism is developed according to static force-based and displacement-based approaches. The main goal is to point out the great importance of the stabilizing role of friction between interlocked walls compared to other extrinsic or intrinsic loading capacities, e.g. the effect of tie-rods and simply supported horizontal diaphragms with frictional resistance. The sensitivity of the load multiplier to these strength parameters is investigated both at the onset of the rocking mechanism and after the hinge formation and a parametric analysis is carried out for the first condition. The results are obtained with reference to different combinations of loading conditions, including the detrimental effect of the static thrust of masonry vaults. Comparative results and pushover curves are developed to evaluate the loading and displacement capacities for each case analyzed and some experimental work is presented to validate the analytical results.